Assessing the applicability of cardiac myosin inhibitors for hypertrophic cardiomyopathy management in a large single center cohort - Amr, Ali; Kayvanpour, Elham; Reich, Christoph; Kölemen, Jan; Asokan, Shamily; Frey, Norbert; Meder, Benjamin; Sedaghat-Hamedani, Farbod (Reviews in cardiovascular medicine, 2024)
Background: Cardiac myosin inhibitors (CMIs), including Mavacamten and Aficamten, have emerged as a groundbreaking treatment for hypertrophic cardiomyopathy (HCM). The results from phase 2 and 3 randomized clinical trials for both drugs have showed promising outcomes. However, the highly selective patient recruitment for these trials raises questions about the generalizability of the observed positive effects across broader patient populations suffering from HCM. Methods: A retrospective cohort study at University Hospital Heidelberg included 404 HCM patients. Baseline assessments included family history, electrocardiograms (ECGs), and advanced cardiac imaging, to ensure the exclusion of secondary causes of left ventricular hypertrophy. Results: Among the HCM patients evaluated, only a small percentage met the inclusion criteria for recent CMI trials: 10.4% for EXPLORER-HCM and 4.7% for SEQUOIA-HCM. The predominant exclusion factor was the stringent left ventricular outflow tract (LVOT) gradient requirement. Conclusions: This study highlights a significant discrepancy between patient demographics in clinical trials and those encountered in routine HCM clinical practice. Despite promising results from the initial randomized clinical trials that led to the approval of Mavacamten, the selected patient population only represents a small part of the HCM patient cohort seen in routine clinics. This study advocates for further expanded randomized clinical trials with broader inclusion criteria to represent diverse primary HCM patient populations.
Gesehen am 13.12.2024